Evaluation of Information Technology Governance Readiness at LKP Karya Prima Based on ISO/IEC 38500 Using the CIPP Model - Muhammad Hasanuddin; Muhammad Amin; Andysah Putera Utama Siahaan (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Effective information technology governance plays an important role in supporting institution goals, including those of non-formal educational institutions. LKP Karya Prima Kursus has implemented information technology to support its operational activities; however, no comprehensive evaluation has been conducted to assess the readiness of its information technology governance. This study aims to evaluate the readiness level of information technology governance at LKP Karya Prima Kursus using the ISO/IEC 38500 framework integrated with the Context, Input, Process, Product (CIPP) evaluation model. The study employed a mixed-methods approach by collecting data through observation, interviews, documentation, and questionnaires distributed to 23 respondents using a total sampling technique. The collected data were analyzed using descriptive statistics based on a Likert scale and interpreted according to the CIPP evaluation components. The findings indicate that the overall readiness level of information technology governance achieved an average score of 2.41, categorized as Less Ready. The evaluation results show that the Context component scored 2.41 (Less Ready), Input scored 2.42 (Less Ready), Process scored 2.14 (Less Ready), while Product achieved the highest score of 2.65 (Moderately Ready). The Process component represents the weakest aspect and should therefore become the primary focus for organizational improvement. This study proposes several recommendations, including the establishment of formal IT governance policies, enhancement of human resource competencies, development of standard operating procedures, implementation of continuous monitoring and evaluation, and alignment of IT strategies with organizational objectives. These recommendations are expected to improve the effectiveness and sustainability of information technology governance implementation at LKP Karya Prima Kursus.